FORMULASI SABUN PADAT EKSTRAK BEKATUL BERAS MERAH (Oryza nivara) DENGAN METODE COLD PROCESS SEBAGAI ANTIBAKTERI TERHADAP Staphylococcus aureus - Ni Luh Gde Mona Monika; Yunita, Ella; Ratih Listiani, Putu Ayu (Institut Teknologi dan Kesehatan Bintang Persada, 2025)
Red Rice Bran (Oryza nivara) is one of the natural ingredients that contains flavonoids, tannins, alkaloids, and terpenoids that are able to provide antibacterial activity. The purpose of this study is to determine the antibacterial activity of solid soap preparations of 96% ethanol extract of brown rice bran by cold process method against Staphylococcus aureus bacteria. The extraction process is carried out by the maceration extraction method, namely by using 96% ethanol solvent. The antibacterial activity test of the extract was carried out using Staphylococcus aureus test bacteria with variations in the concentration of ethanol extract of brown rice bran which were 1.5%, 2.5%, and 3.5%. The antibacterial activity test of solid soap of brown rice bran extract was carried out using Staphylococcus aureus test bacteria with F0, F1, F2 and F3 formulations. The method used for the antibacterial activity test was diffusion with Kirby-baurer disc paper discs using Mueller Hilton agar media. The results of the antibacterial activity test of solid soap preparations of 96% ethanol extract of brown rice bran by cold process method have antibacterial activity with moderate inhibitory power against Staphylococcus aureus bacteria. The inhibition comes from the soap base, the addition of extracts to the 2%, 2.5%, 3% concentration variations does not provide an increase in inhibition against the growth of Staphylococcus aureus bacteria.